EXPLORING STUDENTS' PERSPECTIVES ON TIKTOK CONTENT CREATED BY NIAS CREATORS THAT WEAKENS THE PUBLIC IMAGE OF THE NIAS COMMUNITY - Laoli, Adieli; Zendrato , Oktoberlianus; Zebua , Malili; Laowo, Fitriana Purnamasari; Giawa, Ester Linda Putri (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to explore students' perspectives on TikTok content created by Nias creators that has the potential to weaken the public image of the Nias community. This study uses a qualitative approach with a qualitative descriptive design. The research participants consisted of 15 fifth-semester students from the English Education Study Program at Nias University, who were purposively selected from a total of 37 students. Data were obtained through in-depth interviews and supported by analysis of relevant TikTok content. Data analysis was conducted qualitatively by presenting the results in the form of descriptive narratives. The results showed that students viewed the TikTok content studied as containing elements of inappropriate conversation, coarse language, and violations of social norms that had the potential to form negative perceptions of Nias cultural identity. Students also emphasized the importance of creators' responsibility in representing regional culture and language in the digital space.